Medical negligence, workforce migration, and the sustainability crisis in Malaysia’s public healthcare system - Yasin, Redwan; Sathik, Hassan Basri Jahubar; Haniff, Wan Amir Azlan Wan; Yusof, Zulhazmi (International Journal of Asian Social Science, 2025)
This study explores the increasing strain on Malaysia’s public healthcare system resulting from rising medical malpractice cases, physician migration to the private sector, and long-term sustainability issues. It focuses on the legal, institutional, and workforce challenges contributing to physician burnout and clinical negligence. A doctrinal legal research method and thematic analysis were applied to examine selected Malaysian case law from LexisNexis and relevant academic literature. This approach assesses how courts interpret negligence in overloaded healthcare environments and evaluates the scope of indemnity protections available to public healthcare professionals. Key court rulings reveal that public sector physicians remain personally liable for negligence despite government legal aid, incentivizing migration to private practice. However, private sector employment is not risk-free, as courts increasingly hold private hospitals liable under non-delegable duty principles, challenging assumptions of legal immunity. The evolving legal landscape affects both public and private healthcare practitioners, underscoring the need for clearer liability frameworks and more equitable protections. The study recommends reforming indemnity laws, improving working conditions, and adopting shared liability models. It also calls for stronger intersectoral collaboration and sustainable funding strategies to ensure a resilient, fair, and future-ready public healthcare system in Malaysia.